Carrying a ball can influence sidestepping mechanics in rugby - Brown, S. R.; Brughelli, M.; Hume, P. A. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
Sidestepping mechanics have been implicated as a risk factor for knee injury in rugby. Carrying a ball is proposed to alter movement patterns. Therefore the purpose of the study was to examine the effects of sidestepping with a ball compared to sidestepping without a ball on lower-extremity biomechanics in male rugby athletes. Three-dimensional kinematics of 18 male rugby athletes were recorded during a maximal effort 45° sidestepping task without and with a ball. Sidestepping with a ball resulted in 15% greater knee adduction angle during weight acceptance and 18% greater hip adduction angle during peak pushoff than without a ball. Future biomechanical evaluations of athletes require the inclusion of the ball specific to the sport to ensure accurate interpretation of movement patterns.